Collaboration Between Facilitator and Social Media officer in Introducing Daya Market Through BPTN Syariah's Sahabat Daya Program - Dewi, Kharisma Tri Buana; Oktafia, Renny (PT Inovasi Pratama Internasional, 2024)
The development of increasingly sophisticated technology requires MSME players to understand increasingly sophisticated technology. The development of technology that has brought many changes to society, the emergence of media has its own impact on life in this world. Everyone can use social media easily. In this case, the rapid development of information technology encourages the economy to develop with the existence of Islamic economics in Islamic banks. PT Bank BTPN Syariah Tbk is a company engaged in the Islamic financial sector. One of the programs initiated by BTPN Syariah bank is Pasar Daya, a program owned by BTPN Syariah organized by Daya. The main objective of this program is to maximize the potential of Access to Market (market access) for customers. The method used in conducting this community service program is to use the ABCD (Asset Based Community Development) method.